Vestido de Noiva: The interface between Fashion and Literature through the analysis of the rodriguean play (ModaPalavra e-periódico, 2012)
The present work establishes an interface between Fashion and Literature through the analyses of the play Vestido de Noiva (1943) by Nelson Rodrigues. By naming the play with one of the most representative clothes in the occidental society, Nelson confirms that the connection between these two areas studied in this work. But, beyond describing the clothes of a determined period, Nelson creates his characters and dramas by them. And the wedding dress itself represents the central peace in the play.
Keywords: Fashion; Literature; wedding dress